EKSISTENSI PARTAI POLITIK DI INDONESIA MASA PRA DAN PASCA KEMERDEKAAN - Nadhifatus Shofia; Moch. Zaidan Alamsyafi (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2019)
The political system in Indonesia always has a close relationship with political parties. Basically, the emergence of political parties is the actualization of the various sects or political views that lie behind them. Through a theoretical and law approach, this paper discusses the existence of political parties in Indonesia, especially in the pre and post independence period. The author concludes that in terms of basic ideological aspects, the emergence of Indonesian political parties in the pre-independence era is the actualization of three political streams or views that found momentum in the 20th century. The three streams referred to are Nationalism, Islam, and Marxism/Socialism. After the proclamation of independence, the emergence of the concept of multiple parties gave rise to several new political parties. The formation of political parties after the proclamation of independence is often based on the values or principles of divinity, nationality, and Marxism. However, this does not prevent the emergence of parties that were born based on values or other principles.